Evaluation of work capacity of vocational school students of decorator’s speciality with Ergos II - Daiva Mockevičienė; Ilona Dobrovolskytė (Social Welfare: Interdisciplinary Approach)
The aim of the research – to evaluate the change in work capacity in students of the speciality of decorator applying vocational rehabilitation programmes. The students of the vocational training study programme of the decorator in the vocational training centre (N=10) participated in the research. In performing the present research the method of linear experiment has been chosen. The respondents were evaluated with ERGOSII Work Simulator. Individual rehabilitation programme for training work capacity was created for every respondent and performed for three month time period. After three months the re-evaluation was performed.